Perfection of badminton players' speed-power fitness with the help of training means' variable modules - I.V. Karatnyk; O.O. Hrechanyuk; O.Y. Bubela; M.P. Pityn (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to determine effectiveness of badminton players' speed power fitness program's perfection at stage of specialized basic training with different variants of training means modules' combination. Material: in experiment badminton players of 15-17 years' age (from 1st sports grade to master of sports) participated. The sportsmen were divided into three experimental groups (10 persons in each). The trainings were being conducted during 24 weeks by different variants of program. Results: we created different complexes of exercises, combined in three modules (every of each lasted eight week micro-cycles). Every module has more expressed meaningful parts (1 - speed, 2 - power, 3 - jumping). All modules were combined in program of badminton players' speed power fitness perfection. For every experimental group we worked out distinguishing variant of modules' combination in program (first variant - 1-2-3 modules; second - 2-3-1; third - 3-1-2). General duration of program was 24 week micro-cycles. Conclusions: we recommended some variants of variable modules' combination for badminton players' speed-power fitness perfection. With it, we can regard total influence on the following: speed-power endurance, work with support on own body, quick movements of different body links.